47‐4: Invited Paper: Development of Fast Response, Low Latency Real‐time Camera and Display System for Automotive Applications. Issue 1 (May 2017) - Yamaguchi, Kazunori; Matsushima, Toshiharu; Goto, Fumitaka; Suzuki, Daichi; Nakanishi, Takayuki; Matsushima, Satoshi
Abstract : We have newly developed a Camera Monitoring System (CMS) for automotive side and back mirrors. With improved liquid crystal response time, display brightness, refresh rate and system latency, developed CMS will greatly enhance the safety of driving, compared to the conventional CMS.